Atomic force microscopy in cell biology - Jena, Bhanu P.; Heorber, J. K. Heinrich (Academic Press, 2002)
This is the first book to cover the history, structure, and application of atomic force microscopy in cell biology. Presented in the clear, well-illustrated style of the Methods in Cell Biology series, it introduces the AFM to its readers and enables them to tap the power and scope of this technology to further their own research. A practical laboratory guide for use of the atomic force and photonic force microscopes, it provides updated technology and methods in force spectroscopy. It is also a comprehensive and easy-to-follow practical laboratory guide for the use of the AFM and PFM in biological research.--Provided by publisher.